Play to learn, teach by play. (8th June 2015) - Palagi, Elisabetta; Stanyon, Roscoe; Demuru, Elisa
Abstract: The synthesis provided by Kline in the target article is noteworthy, but ignores the inseparable role of play in the evolution of learning and teaching in both humans and other animals. Play is distinguished and advantaged by its positive feedback reinforcement through pleasure. Play, especially between adults and infants, is probably the platform from which human learning and teaching evolved.